Particle motion and heat transfer in an upward-flowing dense particle suspension: Application in solar receivers. (23rd February 2018) - García-Triñanes, P.; Seville, J.P.K.; Ansart, R.; Benoit, H.; Leadbeater, T.W.; Parker, D.J.
Graphical abstract: Highlights: Particle trajectories are determined within a dense upward-moving fluidised bed. Particle-to-wall heat transfer coefficients have been measured experimentally. Heat transfer coefficients are in the range 180–320 W/m 2 K. Particle residence times at the wall were found to be distributed according to a log-normal distribution. Experimentally-obtained heat transfer coefficients were found to be in good agreement with prior predictions. Abstract: Concentrated solar power (CSP) plants conventionally make use of molten salt as the heat transfer medium, which transfers heat between the solar receiver and a steam turbine power circuit. A new approach uses particles of a heat-resistant particulate medium in the form of many dense upward-moving fluidised beds contained within an array of vertical tubes within the solar receiver. In most dense gas–solid fluidisation systems, particle circulation is induced by bubble motion and is the primary cause of particle convective heat transfer, which is the major contributing mechanism to overall heat transfer. The current work describes experiments designed to investigate the relationship between this solids convection and the heat transfer coefficient between the bed and the tube wall, which is shown to depend on the local particle concentration and their rate of renewal at the wall. Experiments were performed using 65 µm silicon carbide particles in a tube of diameter 30 mm, replicating the conditions used in the real application. Solids motion and time-averaged solids concentration were measured using Positron Emission Particle Tracking (PEPT) and local heat transfer coefficients measured using small probes which employ electrical resistance heating and thermocouple temperature measurement. Results show that, as for other types of bubbling beds, the heat transfer coefficient first increases as the gas flow rate increases (because the rate of particle renewal at the wall increases), before passing through a maximum and decreasing again as the reducing local solids concentration at the wall becomes the dominant effect. Measured heat transfer coefficients are compared with theoretical approaches by Mickley and Fairbanks packet model and Thring correlation. The close correspondence between heat transfer coefficient and solids movement is here demonstrated by PEPT for the first time in a dense upward-moving fluidised bed.